Food allergies are associated with increased disease activity in multiple sclerosis. Issue 6 (18th December 2018) - Fakih, Rami; Diaz-Cruz, Camilo; Chua, Alicia S; Gonzalez, Cindy; Healy, Brian C; Sattarnezhad, Neda; Glanz, Bonnie I; Weiner, Howard L; Chitnis, Tanuja
Abstract : Objective: The association between allergy and multiple sclerosis (MS) is still unclear. In our study, we assessed the association between a self-reported history of allergic conditions with MS clinical and MRI disease activity. Methods: A subset of 1349 patients enrolled in the Comprehensive Longitudinal Investigation of Multiple Sclerosis at the Brigham and Women's Hospital (CLIMB) study completed a self-administered questionnaire on environmental, food and drug allergies. Patients were distributed among four allergy groups: (1) environmental, (2) food, (3) drug, (4) no known allergies (NKA). Clinical (number of attacks, expanded disability status scale (EDSS), MS severity score (MSSS)) and radiological variables (presence of gadolinium-enhancing lesions and lesion count), and their associations with the different allergy groups or those with NKA, were assessed. Results: The food allergy group had a 1.38 times higher rate for cumulative number of attacks compared with the NKA group (P=0.0062); this difference remained significant in the adjusted analysis (relapse rate ratio 1.27, P=0.0305). The food allergy group showed more than twice the likelihood (OR 2.53, P=0.0096) of having gadolinium-enhancing lesions on MRI. The environmental and drug allergy groups did not show significant differences when compared with the NKA group. The EDSS and MSSS were not affected by any type of allergy. Conclusions: MS patients with food allergy had more relapses and a higher likelihood of gadolinium-enhancing lesions compared with patients with no known allergy. Future prospective studies are needed to confirm our findings and investigate underlying biological mechanisms, which may unveil new therapeutic and preventative strategies for MS.